2011
DOI: 10.1292/jvms.11-0153
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Total Intravenous Anesthesia Using a Combination of Propofol and Medetomidine following Anesthesia Induction with Medetomidine, Guaifenesin and Propofol for Castration in Thoroughbred Horses

Abstract: ABSTRACT. Seven Thoroughbred horses were castrated under total intravenous anesthesia (TIVA) using propofol and medetomidine. After premedication with medetomidine (5.0 g/kg, intravenously), anesthesia was induced with guaifenesin (100 mg/kg, intravenously) and propofol (3.0 mg/kg, intravenously) and maintained with constant rate infusions of medetomidine (0.05 g/kg/min) and propofol (0.1 mg/kg/min). Quality of induction was judged excellent to good. Three horses showed insufficient anesthesia and received a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…, ; Oku et al. ). Ketamine is an effective anesthetic and analgesic agent in horses, but also requires to be given with other drugs such as alpha 2 ‐adrenergic agonists to reduce any adverse effects such as muscle rigidity and excitement (Mama et al.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…, ; Oku et al. ). Ketamine is an effective anesthetic and analgesic agent in horses, but also requires to be given with other drugs such as alpha 2 ‐adrenergic agonists to reduce any adverse effects such as muscle rigidity and excitement (Mama et al.…”
Section: Introductionmentioning
confidence: 98%
“…Its use in larger animals as the sole anesthetic agent is limited by the low concentration of the available commercial formulation to deliver an appropriate infusion rate and by its lack of analgesic properties, resulting in unacceptable induction and anesthetic qualities (Mama et al 1995(Mama et al , 1996. Techniques have been developed to reduce the amount of propofol required, prevent physiological responses to surgery and yet still make use of the anesthetic and rapid recovery properties of propofol (Bettschart-Wolfensberger et al 2003, 2005aOku et al 2011). Ketamine is an effective anesthetic and analgesic agent in horses, but also requires to be given with other drugs such as alpha 2adrenergic agonists to reduce any adverse effects such as muscle rigidity and excitement (Mama et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that desflurane causes vasodilation in subcutaneous tissues, changes in heart rate and respiration, and decreased body temperature [17,21]. The decrease in body temperature of the horses was usually dependent on skin thickness and ambient temperature 25].…”
Section: Resultsmentioning
confidence: 99%
“…Prassinos et al (2005) determined that the use of ketamine and propofol for the induction of anaesthesia in goats led to hypoxemia, which resulted from respiratory failure trigerred by the anaesthetics used. Oku et al (2011) indicated that, in horses, as a result of a decreased respiratory rate throughout propofol-medetomidine anaesthesia, the PaO 2 level decreased and the PaCO 2 level increased. Cullen and Reynoldson (1997) reported that propofol decreased PaO 2 levels and increased PaCO 2 levels, whilst Keegan et al (1993) observed that propofol did not cause any alteration in PaO 2 and PaCO 2 levels.…”
Section: Blood Gases and Electrolyte Levelsmentioning
confidence: 99%
“…Research has been conducted in several species on the impact of various anaesthetic agents on the antioxidant system and blood gases (Kamiloglu et al, 2009;Mannarino et al, 2012;Oku et al, 2011). However, to the authors' knowledge, the impact of the combinations of xylazine with ketamine and propofol on the antioxidant status and blood gas levels has not been investigated before in sheep.…”
Section: Introductionmentioning
confidence: 99%